"Attention everyone, time out!": safety attitudes and checklist practices in anesthesiology in Germany : a cross-sectional study - Neuhaus, Christopher; Spies, Aline; Wilk, Henryk; Weigand, Markus A.; Lichtenstern, Christoph (Journal of patient safety, 2021)
The use of perioperative checklists has generated a growing body of evidence pointing toward reduction of mortality and morbidity, improved compliance with guidelines, reduction of adverse events, and improvements in human factor-related areas. Usual quality management metrics generally fall short in assessing compliance with their perioperative application. Our study assessed application attitudes and compliance with safety measures centered around the World Health Organization (WHO) "Safe Surgery Saves Lives" campaign as perceived by anesthesia professionals in Germany.